2021
DOI: 10.3390/genes12030440
|View full text |Cite
|
Sign up to set email alerts
|

The Important Role of N6-methyladenosine RNA Modification in Non-Small Cell Lung Cancer

Abstract: N6-methyladenosine (m6A) is one of the most prevalent epigenetic modifications of eukaryotic RNA. The m6A modification is a dynamic and reversible process, regulated by three kinds of regulator, including m6A methyltransferases, demethylases and m6A-binding proteins, and this modification plays a vital role in many diseases, especially in cancers. Accumulated evidence has proven that this modification has a significant effect on cellular biological functions and cancer progression; however, little is known abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 128 publications
0
11
0
Order By: Relevance
“…As the most abundant mRNA modification, m6A is involved in the regulation of the occurrence and development of tumors by controlling the expression of key genes, which has become the focus of research in recent years ( Zhao et al, 2020 ). Previous studies have reported that abnormal m6A methylation modification may impact the development of lung cancer ( Cheng et al, 2021 ). Our result showed that there are nine m6A-related regulators that were differentially expressed between high- and low-DNASE1L3 expression of LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…As the most abundant mRNA modification, m6A is involved in the regulation of the occurrence and development of tumors by controlling the expression of key genes, which has become the focus of research in recent years ( Zhao et al, 2020 ). Previous studies have reported that abnormal m6A methylation modification may impact the development of lung cancer ( Cheng et al, 2021 ). Our result showed that there are nine m6A-related regulators that were differentially expressed between high- and low-DNASE1L3 expression of LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…The m 6 A modification of RNA, mediated by demethylases, methyltransferases, and m 6 A-binding molecules, influences the progress of NSCLC by affecting the target RNA splicing, translation, decay, and nuclear export. It has been recommended that the influence of m 6 A modification on the prognosis of NSCLC patients is a double-edged sword, indicating m 6 A modification has both promotive and inhibitory effects on progress of NSCLC ( 173 ). CircRNAs are a class of conserved single-stranded RNA molecules derived from intronic or exonic sequences by back-splicing of precursor mRNA, and have been described to have effects on microRNA sponges, regulators of gene splicing and transcription, RNA-binding protein sponges, and protein/peptide translators ( 174 ).…”
Section: Epigenetics In the Innovative Diagnostic And Therapeutic Str...mentioning
confidence: 99%
“…21 However, little is known about the precise mechanisms of the post-transcriptional regulation of TLR4 expression regulation in the PVN post-MI. N6-methyladenosine (m 6 A) is the most abundant mRNA and epigenetic modification 22,23 that occurs at the post-transcriptional level in mammals. m 6 A is installed onto target mRNA through m 6 A regulators which include the m 6 A methyltransferase complex (METTL3, METTL14, WTAP, VIRMA, RBM15 and ZC3H13) 24 and is enriched near the stop codon, 3′-untranslated region (3′UTR) 25 and long internal exon, primarily occurring in the RRACH sequence (where R = G or A; H = A, C or U) of mRNA.…”
Section: Introductionmentioning
confidence: 99%